2008
DOI: 10.1007/s10554-008-9337-x
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular volumes and mass in marathon runners and their association with cardiovascular risk factors

Abstract: Increases in LVMM and LVEDV may not only represent a response to exercise but are dependent on age and blood pressure, also. In addition, a left ventricular hypertrophy without an increase in volume may be an indicator for early subclinical cardiac alterations in response to risk factor exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…During the postexercise period, the cardiac geometric dimensions are restored, but with this recurrent stretch of the chambers and reestablishment of the chamber geometry, some individuals may be prone to the development of chronic structural changes including chronic dilatation of the RV and RA with patchy myocardial scarring in response to the recurrent volume over- load and excessive cardiac strain. [17][18][19]29,44 These abnormalities are often asymptomatic and probably accrue over many years; they might predispose to serious arrhythmias such as atrial fibrillation and/or ventricular arrhythmias (VAs).…”
Section: Biomarker Evidence For Cardiac Damage With Extreme Endurance Etmentioning
confidence: 99%
See 1 more Smart Citation
“…During the postexercise period, the cardiac geometric dimensions are restored, but with this recurrent stretch of the chambers and reestablishment of the chamber geometry, some individuals may be prone to the development of chronic structural changes including chronic dilatation of the RV and RA with patchy myocardial scarring in response to the recurrent volume over- load and excessive cardiac strain. [17][18][19]29,44 These abnormalities are often asymptomatic and probably accrue over many years; they might predispose to serious arrhythmias such as atrial fibrillation and/or ventricular arrhythmias (VAs).…”
Section: Biomarker Evidence For Cardiac Damage With Extreme Endurance Etmentioning
confidence: 99%
“…Although it has been recognized that elite-level endurance athletes commonly have electrocardiographic abnormalities and atrial and ventricular ectopy, 28,44,54 these functional adaptations traditionally have not been thought to predispose to serious arrhythmias or SCD. However, it appears that adverse cardiac remodeling induced by excessive ET can create an arrhythmogenic substrate, and rhythm abnormalities may be the most common CV problems encountered by veteran endurance athletes.…”
Section: Proarrhythmic Effects Of Excessive Endurance Etmentioning
confidence: 99%
“…In line with this hypothesis, the investigators of the Heinz Nixdorf Recall Study [38,39] showed that 108 apparently healthy marathon runners (older than 50 years) presented a similar CAC distribution of age-matched controls (median CAC: 36 vs 38 Agatston Units, p = 0.36, respectively) but greater CAC burden than peers matched by the Framingham risk score (median CAC: 36 vs 12 Agatston Units, p = 0.02, respectively) [38]. Of importance, the event-free survival was inversely related to CAC burden during a mean follow-up of 21.3 ± 2.8 months [38], suggesting that CAC portends a poor prognosis and is an early indicator for subclinical cardiac alteration even in this apparently super-healthy population [39,40,41]. …”
Section: Pa and Markers Of Subclinical Atherosclerosis In The Generalmentioning
confidence: 97%
“…Both imaging modalities have been shown to play a pivotal role in the accurate evaluation of left ventricular function particularly in patients with ischemic heart disease and different forms of cardiomyopathy [2136]. These methods are needed to accurately identify and characterize patients with various manifestations of left ventricular hypertrophy (LVH) [37–49].…”
mentioning
confidence: 99%